2019
DOI: 10.3390/cancers11081133
|View full text |Cite
|
Sign up to set email alerts
|

Atypical BRAF and NRAS Mutations in Mucosal Melanoma

Abstract: Primary mucosal melanomas represent a minority of melanomas, but have a significantly worse prognosis than cutaneous melanomas. A better characterization of the molecular pathogenesis of this melanoma subtype could help us understand the risk factors associated with the development of mucosal melanomas and highlight therapeutic targets. Because the Mitogen-Activated Protein Kinase (MAPK) pathway plays such a significant role in melanoma development, we explore v-raf murine sarcoma viral oncogene homolog B (BRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 64 publications
3
51
0
2
Order By: Relevance
“…Approximately 7%-22% of MMs have v-kit Hardy-Zuckerman 4 feline sarcoma viral oncogene homolog (KIT) somatic mutations or amplifications (Dumaz et al, 2019;Tyrrell & Payne, 2018). MMs located in the genital area appear to be driven by mutations in SF3B1 which encodes the subunit 1 of splicing factor 3b, a component of the spliceosome that processes pre-mRNA into mature transcripts (Furney et al, 2013;Oiso, Sakai, Yanagihara, Nishio, & Kawada, 2018;Quek et al, 2019).…”
Section: Mutational/molecular Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 7%-22% of MMs have v-kit Hardy-Zuckerman 4 feline sarcoma viral oncogene homolog (KIT) somatic mutations or amplifications (Dumaz et al, 2019;Tyrrell & Payne, 2018). MMs located in the genital area appear to be driven by mutations in SF3B1 which encodes the subunit 1 of splicing factor 3b, a component of the spliceosome that processes pre-mRNA into mature transcripts (Furney et al, 2013;Oiso, Sakai, Yanagihara, Nishio, & Kawada, 2018;Quek et al, 2019).…”
Section: Mutational/molecular Profilementioning
confidence: 99%
“…Mucosal melanoma (MM) is one of the rarest types of melanoma, accounting for only 1% of all cases (Dumaz et al., 2019; McLaughlin et al., 2005), and has a significantly worse prognosis relative to the other subtypes (Dumaz et al., 2019). Distinct from cutaneous melanoma, MM arises from melanocytes located in mucosal membranes inside the body (i.e., genitourinary, anorectal, nasopharyngeal; Dumaz et al., 2019). The head and neck (55), vulva (18), and anus (24) are the most common observed sites; however, MM can also occur in the gut, lungs, and urinary track (Figure 2; Chang, Karnell, & Menck, 1998).…”
Section: Mucosal Melanoma: One Of the Rarest Forms Of Malignant Melanomamentioning
confidence: 99%
“…BRAF mutations are present in MM but at a lower frequency (6–12%) compared to CM [ 113 , 114 , 115 ]. In a whole-genome sequencing analysis of 67 MM samples performed by Newell et al, BRAF mutations were most commonly found in the protein tyrosine kinase domain, with V600E, V600K, and V600R being the most common BRAF mutations [ 116 ].…”
Section: Mucosal Melanomamentioning
confidence: 99%
“…On the other hand, non-V600 mutations appear to be present in a higher proportion in MM. In this context, a compiled BRAF mutation analysis of 1339 MM performed by Dumaz et al showed that 37% of mutations were placed on another codon different from V600, particularly on D594 (40%), G469 (24%), and K601 (16%) [ 113 ].…”
Section: Mucosal Melanomamentioning
confidence: 99%
See 1 more Smart Citation